Outcome After Surgery of Recurrent Lumbar Disc Disease - Salman A Jaffery , (Journal of Rawalpindi Medical College, 2013)
Background: To assess the outcome after surgery of recurrent lumbar and sciatic pain in a patient population where long term nonsurgical measures have failed. Methods: Out of 145 lumbar discectomies , 21 patients underwent reoperation after failure of lumbar disc surgery to relieve pain. All patients underwent MRI lumbosacral spine and when needed enhanced with gadolinium. The surgical procedure was reexploration of the previous operation site, extension of the exposure by either hemilaminectomy or laminectomy. The standard surgical technique with extensive tissue dissection to expose and extradural exploration with excision of scar and herniated material was employed. . The relation of the herniated material with the nerve root in the extradural canal was also noted. Loupes with × 3.5 magnification and fiberoptic lighting were used in 13 of 21 cases. Postoperative leg pain was assessed using VAS mean leg score preoperatively, on 3rd postoperative day and the 7th postoperative day Results: Pain recurred in 57.14% after 1 year. Pain recurred in the same leg in 66.66%, in contralateral leg in 23.80%, and in both legs in 9.52 %. Fourteen patients (66.66%) experienced Lumbar Disc Herniation (LDH) recurrence following single level discectomy. The most common level involved was L4-L5 (11 cases) and the mean length of time to recurrence was 12 weeks. Postoperative pain scores were better than Preoperative scores when compared. Conclusions: The likelihood that reoperation would relieve pain was less than the original surgery. Excision of scar alone or dorsal root resection (Rhizotomy) was of no value in these cases.